AVOID THE ERROR IN THE USE CONJUNCTION IN SENTENCES - Najamuddin N (El-Tsaqafah : Jurnal Jurusan PBA, 2017)
Sometimes too many conjunctions because we do not rememberexactly how many clauses we have written. Therefore before make sure thatwe have the correct number of clauses. This part contains the necessaryconjunction In grammar, a conjunction (abbreviated CONJ or CNJ) is a partof speech that connects words, phrases, or clauses that are called the conjunctsof the conjoining construction. The term discourse marker is mostly usedfor conjunctions joining sentences. This definition may overlap with that ofother parts of speech, so what constitutes a “conjunction” must be definedfor each language. In general, a conjunction is an invariable grammaticalparticle and it may or may not stand between the items in a conjunction.Conjunction is used to make a sentence which having the cohesion andcoherence in text. The absence of the right conjunction will result in havingillogical meaning, and the message. Because of the important role ofconjunctions in the writing process, this study aims to reveal the students’common errors on the use of conjunction in their writing, and investigatetypes of errors that occur most frequently in students’ writing